Productive Zakat Distribution at National Amil Zakat Agency (BAZNAS) of Tanjungpinang City: A Review Based on Indonesia’s Minister of Religious Affairs Regulation No. 52 of 2014 - Mario Rahmad Adi Pratama; M. Arbisora Angkat; M. Azmi (Advances in Humanities and Contemporary Studies, 2026)
This study examines the system of distributing productive zakat at the National Amil Zakat Agency (BAZNAS) of Tanjungpinang City in 2021, reviewed based on the Regulation of the Minister of Religious Affairs of the Republic of Indonesia Number 52 of 2014. The purpose of this study is to determine the implementation of productive zakat distribution and its compliance with sharia principles and applicable regulations. The research method used is descriptive qualitative, employing interviews, observation, and documentation. The results show that the distribution of productive zakat has been carried out in accordance with sharia principles after the basic needs of the beneficiaries (mustahik) are fulfilled. The programs implemented include assistance in the form of carts, business capital, business equipment, and facilities for fishermen, with priority given to the poor (fakir), the needy (miskin), and converts (muallaf). However, there are obstacles in the aspects of mentoring and supervision, which have not been optimal, resulting in some beneficiaries’ businesses not developing. The efforts made by BAZNAS include re-collecting data on beneficiaries and providing additional assistance for businesses that are still running. In conclusion, the system of productive zakat distribution at BAZNAS Tanjungpinang City is in accordance with regulations, but still requires improvement in mentoring and supervision.